Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae) - Verheye, Marie L.; Lörz, Anne-Nina; D‘acoz, Cédric D’udekem (Zootaxa, 2018)
A new crested amphipod, Epimeria cleo sp. nov., is described after specimens collected in the western Ross Sea, Southern Ocean, at 151–409 m depth. This increases the number of Epimeria species known from the Ross Sea to eleven. This new species belongs to the subgenus Drakepimeria d’Udekem d’Acoz & Verheye, 2017. E. cleo sp. nov. has very robust walking pereiopods, no mid-dorsal tooth or bump on pereonites 1–2, no lateral tooth or angle on the lateral carina of coxa 4 and no pair of small teeth pointing upwards on urosomite 2. It is morphologically very similar to Epimeria leukhoplites d’Udekem d’Acoz & Verheye, 2017, E. reoproi Lörz & Coleman, 2001 and E. vaderi Coleman, 1998, the latter three species being known only from the Antarctic Peninsula and South Shetland Islands. Epimeria cleo sp. nov. can be distinguished from them by the following combination of characters: flexed rostrum, narrow coxa 3, long ventral tooth on coxa 4 and non-duplicate lateral tooth on pleonites 1–2. The phylogenetic relationships between E. cleo sp. nov. and other Epimeria of the subgenus Drakepimeria, for which DNA sequences are available, are briefly outlined based on a phylogenetic analysis of 28S rDNA fragments.